THE EFFECT OF GROUP RESUME METHOD ON STUDENTS WRITING RECOUNT TEXT (A Study at The Tenth Grade Students of SMA Negeri 6 PADANGSIDIMPUAN) - Sonya Cristina (JURNAL LINER (Language Intelligence and Educational Research), 2019)
Abstract: The aims of the research is to know the application of group resume method on students writing recount text ability at the tenth grade of SMA Negeri 6 Padangsidimpuan to know before and after use group resume at the tenth grade of SMA Negeri 6 Padangsidimpuan, and to know whether there is any significant effect of group resume method on students writing recount text ability at the tenth grade of SMA Negeri 6 Padangsidimpuan. The population in this research is all of the tenth grade students are 124. The sample are 27 students which taken by systematic sampling.The research method is use by experimental method. Collecting the data by observation sheet and test as an instrument. The result mean score of the application group resume method is 3.5, based on the technique of analysis data the criterion of score group resume with categorized “Very Good”. To know the result of the data, the researcher analysis data by use the formula of ttest. The result of the data analysis show that of ttest = 6,73, meanwhile ttable 2.06. It means that ttest is higher than ttable. It means that there is significant effect of group resume method on students’ writing recount text abiliy at the tenth grade of SMA Negeri 6 Padangsidimpuan.